2017
DOI: 10.1111/iju.13417
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from the management of adults who have undergone augmentation for spina bifida and bladder exstrophy: Incidence and management of the non‐lethal complications of bladder augmentation

Abstract: The present review provides clinical insights and makes recommendations regarding patient management garnered by the long-term follow up of patients undergoing enteric bladder augmentation for the management of congenital anomalies. A prospectively maintained database on 385 patients that have experienced an enteric bladder augmentation, using either the ileum or colon, was reviewed. Evaluations included methods used to prevent bladder calculi formation and recurrence, the incidence and etiology of renal calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 74 publications
0
24
0
Order By: Relevance
“…A study of pediatric patients who had undergone augmentation cystoplasty with a catheterizable channel showed that complications related to the channel were dependent on the type of channel. 16 Rates of channel abandonment and revisions were highest in patients with a reconfigured ileum (Monti), lower in patients with an appendicovesicostomy (Mitrofanoff), and lowest in patients with a tapered ileum and reinforced ileocecal valve (CCIC). 16 In a similar study, O'Connor et al 17 evaluated the outcomes of different types of catheterizable channels and found that 39% of patients underwent a major channel revision during a median follow-up period of 60 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of pediatric patients who had undergone augmentation cystoplasty with a catheterizable channel showed that complications related to the channel were dependent on the type of channel. 16 Rates of channel abandonment and revisions were highest in patients with a reconfigured ileum (Monti), lower in patients with an appendicovesicostomy (Mitrofanoff), and lowest in patients with a tapered ileum and reinforced ileocecal valve (CCIC). 16 In a similar study, O'Connor et al 17 evaluated the outcomes of different types of catheterizable channels and found that 39% of patients underwent a major channel revision during a median follow-up period of 60 months.…”
Section: Discussionmentioning
confidence: 99%
“…16 Rates of channel abandonment and revisions were highest in patients with a reconfigured ileum (Monti), lower in patients with an appendicovesicostomy (Mitrofanoff), and lowest in patients with a tapered ileum and reinforced ileocecal valve (CCIC). 16 In a similar study, O'Connor et al 17 evaluated the outcomes of different types of catheterizable channels and found that 39% of patients underwent a major channel revision during a median follow-up period of 60 months. The channel incontinence and revision rates were higher in the ileal group than in the appendiceal group, though most of the ileal group had Monti channels and none of them underwent a CCIC.…”
Section: Discussionmentioning
confidence: 99%
“…After performing a Kock pouch, the incidence rises to more than 40% (108). Regular and generous irrigation of the pouch can probably reduce the rate of stones (109). The third most common pouch-related complication is the development of a stenosis at the ureteral re-implantation site.…”
Section: Continent Cutaneous Urinary Reservoirsmentioning
confidence: 99%
“…Common post-operative complications include bladder stones, bladder rupture, renal deterioration, metabolic abnormalities, and malignancy. [3][4][5][6][7][8][9][10] Due to a decreased incidence of associated congenital disorders in the western world as well as improvements in early detection and treatment of patients with neurogenic bladders, the rates of augmentation cystoplasty performed appear to be declining in both the United Kingdom and the United States. 3,4 To our knowledge there have been no Canadian series reporting on long-term outcomes of pediatric bladder augmentation.…”
Section: Introductionmentioning
confidence: 99%